INVESTMENT OPPORTUNITY SET, KONSERVATISME, ALOKASI PAJAK ANTAR PERIODE DAN KUALITAS LABA: INVESTMENT OPPORTUNITY SET, CONSERVATISM AND TAX ALLOCATION BETWEEN PERIODS AND PROFIT QUALITY - Rahman, Diaur; Tumirin, Tumirin (Universitas Riau, 2025)
This study aims to analyze the impact of investment opportunity sets, conservatism, and tax allocation between periods on the quality of profits in manufacturing companies. This study uses a descriptive method with a quantitative approach, analyzed using multiple linear regression techniques through SPSS version 22.00. The population in this study is manufacturing companies in the basic and chemical industries, which were verified on the IDX in 2020-2022. The sample was taken by applying the purposive sampling method, which produced a sample of 38 companies, so that 114 observations were obtained. The results of the assessment stated, where investment opportunity set is not able to affect the quality of profits, while conservatism and tax allocation between periods are able to affect the quality of profits.